Religious Communication of Sunni-Shi'i in Resolving Internal Religion Conflict in North Sumatra - Hasyimsyah Nasution; Suwardi Lubis; Abdul Khalik (Budapest International Research and Critics University, 2021)
The purpose of this study was to find and study about model religious communication and Sunni-Syi'i Conflict in Social Media in Making Harmonist Relationships in North Sumatera. This research will start from the interpretive paradigm. In this paradigm view, human beings are